# 6n+n=

## Simple and best practice solution for 6n+n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6n+n= equation:

Simplifying 6n + n = 0 Combine like terms: 6n + n = 7n 7n = 0 Solving 7n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '7'. n = 0 Simplifying n = 0

### See similar equations:

| 5(8+3f)+f= | | 2s-6s= | | -6x-31=41 | | x^2+3x-20=8 | | -3m+2=-4 | | 4(9z+4)= | | x^2-9x-3=-7x+5 | | -84+9x=-192 | | -t-2t= | | 8.80=0.10x+1.80 | | 3b-9b= | | 9-8x=35+2x | | 7x-15=48 | | 6x^2+25x+11=0 | | 31=-8a+7 | | 7(2s+8)+2s= | | 2-(8x+7)=31+2(x+2) | | 167+18x=-49 | | 33=12a-3 | | n^2-n-12=0 | | -49-4x=-145 | | 8(4+3y)= | | 3(3+8b)+4b= | | -68+11x=-277 | | 4x^2-19x-5=0 | | -3x-35=-86 | | 8.5x-4.3=3.3x+3.5 | | 6m^2+12m-144=0 | | -6(8y+8)+-7(y+8)= | | 6.7x-24=4.4x-7.9 | | 4(7+t)+3t+7= | | 2n^2-2n-112=0 | | 9-12=81x | | 0.6x+.4=0.01x+2 | | 7x-30=4x+18 | | 21+m+y=180 | | 3p^2-27p+24=0 | | 4x^2+5x+9=7x+4 | | 0.01x+4=.02x+0.8 | | 21+y+m=180 | | 5m^2-5m-60=0 | | y+9=4-6y | | 0.01x+4=.02x+0.81 | | 2+12x=x | | 4n^2+n+3=7 | | 3(-9C-2)= | | 5*0-2y=10 | | 5x-2*0=10 | | -3x^2+6x+30=0 | | 2x+18=124 | | 6m+22=9m-5 | | 6Y+3(7+-7Y)+y+2y= | | 8x+2(-4x+11)=13 | | 3x-2=136 | | 2y-3x-9=-4 | | 4a+7+2a= | | 3x+20+x=180 | | 2y-(3x-9)=-4 | | 0.5x-5=1 | | 4(p+7)= | | 6n^2+5n-144=0 | | 2x-3x-9=-4 | | 0.2x+0.3=0.75 | | 15+10x=3+10x+12 | | 2x-(3x-9)=-4 |